A rare case of late developing anti-E antibody in a pregnant female leading to severe hemolytic disease of the newborn: A missed follow-up in COVID-19 epoch - Suhasini Sil; Daljit Kaur; Poonam Singh; Dixa Kumari; Ashish Jain; Gita Negi (Asian Journal of Transfusion Science)
With the use of Anti-D prophylaxis for rhesus D-negative pregnant women, other Rh and non-Rh allo-antibodies have become relatively more important. The index case reports severe hemolytic disease of the newborn due to anti-E antibody in a full-term baby boy born to a COVID-19-positive mother. The antibody screening of the mother performed during Booking of pregnancy at 9th week of gestation was negative. Subsequently the mother was lost to follow-up till delivery due to COVID pandemicity. At birth, the baby was icteric but non-hydropic, his direct antiglobulin test (DAT) was strong positive (4+ by column agglutination technology) and required top-up transfusion and phototherapy at Neonatal Intensive Care Unit. Elution of DAT-positive red cells rendered anti-E which could have formed as “late developing” red cell allo-anti-E in the pregnancy. A repeat antibody screening around 28th week gestation is of prime importance to detect any underlying allo-antibody in a multigravida and thus enabling close monitoring of fetus and initiation of early management as desired.